2016
DOI: 10.3390/ma9121027
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Ti—B Composites Synthesized by Combustion Followed by High-Temperature Deformation

Abstract: Long compact cylindrical rods, which consist of a titanium monoboride-based TiB—30 wt % Ti ceramic composite material, are synthesized during combustion of the initial components (titanium, boron) followed by high-temperature deformation. High-temperature deformation is found to affect the orientation of the hardening titanium monoboride phase in the sample volume and the phase composition of the sample. The combustion temperature is studied as a function of the relative density of the initial workpiece under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…The final composition varies depending on temperature W T . The second example illustrates the capability of the model with detailed reaction scheme (2). In this case we have the heat balance equation in the form similar to [6].…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The final composition varies depending on temperature W T . The second example illustrates the capability of the model with detailed reaction scheme (2). In this case we have the heat balance equation in the form similar to [6].…”
Section: Examplesmentioning
confidence: 99%
“…SHS-methods can be used in composite synthesis [1][2][3][4][5]. The volume synthesis or the synthesis in the explosion mode obeys some preference in comparison with the mode of layerwise combustion, since, for this mode, the best homogenization of synthesized product is observed and it is possible to control the process of changing the conditions of the thermal contact between the reacting system and the environment and between the reacting system and the heater.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has demonstrated that the mechanical properties of stainless steels [15] and of alloys of magnesium [16], cobalt–chromium–molybdenum [17], and titanium [18,19,20,21,22,23,24,25,26,27,28,29,30] can all be improved via the addition of boron. The combination of titanium and boron generates whiskers of titanium boride (TiB) as a result of the reaction Ti + TiB 2 → 2 TiB.…”
Section: Introductionmentioning
confidence: 99%
“…Наибольшее количество исследований посвящено методу СВС-компактирования в песчаной пресс-форме [1,2]. Также известно о работах по прессованию продуктов синтеза в жесткой пресс-форме [3] и «свободным сжатием» [4][5][6].…”
Section: Introductionunclassified